Total Body Surface Area Adjusted Daily Diagnostic Blood Loss May Be Higher in Minor Burns-Are Our Patients the Victims of Daily Routine? - Christian Smolle; Anna Alexandra Elisabeth Persson; Caroline Lind; Fredrik Huss (MDPI AG, 2024)
Burns are common and devastating injuries, often necessitating intensive care treatment and long-term hospitalisation, making burn patients susceptible to hospital-acquired anaemia and blood transfusion. The purpose of this study was to assess diagnostic blood loss in burn patients at the burn intensive care unit (BICU) at Uppsala University Hospital between 1 September 2016 and 30 June 2019. Medical records were screened; age, gender, mechanism, % total body surface area (TBSA), Baux score, length of stay, days on the respirator, days of continuous renal replacement therapy, number of operations, and number of blood tests per patient were assessed. Volume per blood test was estimated as the volume needed for the specific test tube. A total of 166 patients were included in the study. The mean TBSA was 18.0% ± 20, and the mean length of stay was 17.0 ± 41 days. Median diagnostic blood loss was 13.1 mL/day/patient (IQR 7.0, 23.9) and correlated positively with burn extent, Baux score, and mortality. Daily diagnostic blood loss/%TBSA/patient was 1.2 mL (IQR 0.7, 2.3). Transfusion of blood products occurred in 73/166 patients (44%). In conclusion, diagnostic blood loss is greatly influenced by TBSA extent. The diagnostic blood loss can reach significant levels and may affect the transfusion rate.